National discourses, fragments of otherness, and the denial of gaze: Representational minimization and simplification of the Other in pro-migrant media texts - Lymperi, Maria; Archakis, Argiris (Aegean Working Papers in Ethnographic Linguistics, 2025)
This paper investigates the social representation of migrants in western/European discourses. Our main claim is that the video texts under study, although explicitly pro-migrant, do not affirm the realities of migrants, but rather seem to draw more on national and western-oriented discourses, thus providing a calculated projection of visibility to migrants. That is, the video texts overrepresent a “tolerable”, “simplified” migrant who is socioculturally and linguistically familiar with the European/western audience. This familiar and thus tolerable migrant seems to be in contrast with some distant, vague and threatening “intolerable” Others, who remain largely minimized, delegitimized, and denied a gaze in advance. The racist background of this process is deconstructed on the basis of two theoretical premises: a) that the stereotypical representation of the “Other as threat” often continues to underpin pro-migrant discourses when they are articulated in terms of tolerance; and b) that such discursive scaffolding is more implicit, pushed to the margins of the representations that sustain these discourses and involves a more or less fragmented representation of otherness. The language and the degree of explicitness and marginality of such representations will be explored in our data through a discursive analysis based on the categories of highlighting and minimization respectively, which will be conceptualized drawing upon van Leeuwen’s (2008) framework.